SEKAPUR SIRIH TELAAH UNDANG-UNDANGNO.20 TAHUN 2011 TENTANG RUMAH SUSUN - R. Suharto, R. Suharto (Diponegoro Private Law Review, 2019)
ABSTRACT  Housing development for residential in the form of apartments can reduce land use and make open space more spacious is an alternative. A plot of land can be used optimally to become a multi-storey residence that can accommodate as many people as possible. The legal basis for Apartment Development is UU No. 20 year 2011 about apartments, as the substitute of previous Undang-Undang, which is Undang-Undang No. 16 year 1985 about Apartments. The concept of Apartments that had previously been regulated in Undang-Undang No. 16 year 1985 was the concept of Condominium which was adopted and stated in the new constitution. Condominium refer to one form of ownership involving more than one owner.  Keywords : Apartments, Undang Undang No. 20 Year 2011, Study